1987
DOI: 10.1111/j.1365-2621.1987.tb14060.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Production in Staling Beer

Abstract: Levels of ethylene in the headspace of three brands of staling lager beers which were allowed to stale at 40°C increased with storage time. TBA values and browning of staling beers also increased with storage time and coincided with increase in ethylene production. Results indicated that measurement of ethylene in the headspace of beer might be useful to follow beer staling. INTRODUCTIONThe development of stale flavor in beer during storage has been a major problem in the brewing industry. Studies indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The effect of CaNa,EDTA on light-induced oxidation of pickle components was further observed from its inhibition of ethylene production. Ethylene levels have been shown to coincide with TBARS content during stale flavor development of beer (Lynch and Seo 1987). Based on the results in this study, it appears that ethylene may be useful for rapid evaluation of the efficacy of antioxidants.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The effect of CaNa,EDTA on light-induced oxidation of pickle components was further observed from its inhibition of ethylene production. Ethylene levels have been shown to coincide with TBARS content during stale flavor development of beer (Lynch and Seo 1987). Based on the results in this study, it appears that ethylene may be useful for rapid evaluation of the efficacy of antioxidants.…”
Section: Discussionmentioning
confidence: 89%
“…Although methane, ethane, ethylene, propane and propylene were present in all samples, regardless of treatment, only ethylene consistently increased in tissues exposed to light. Ethylene has previously been reported to be an indicator of lipid oxidation (Lynch and Seo 1987). In pickle tissues, light-induced ethylene and TBARS production was reduced more than 50% by 50 ppm CaNa,EDTA and almost completely inhibited by 100 ppm.…”
Section: Effect Of Canaedta On Lipid Oxidationmentioning
confidence: 97%
“…Bitterness is 50 times the absorbance of beer measured in a 1-cm cell using a monochromatic light with a wavelength of 275 nm; it is expressed in a bitterness unit (BU). Simultaneously, 8 trained panelists performed a sensory evaluation of degree of oxidation, quality of bitterness, and sensory stability (Linch and Seo 1987) using a category scale of 1 to 5 (Table 1). One score under 3 is unacceptable.…”
Section: Sensory and Nutritive Qualities Of Foodmentioning
confidence: 99%
“…Many factors affect the intensity of such changes, among them oxygen content, temperature, and storage time. These factors also modify certain important characteristics such as carbon dioxide content, pH, color, turbidity, bitterness, and degree of oxidation, which directly influence the sensory quality of beer (Grisby and others 1974;Linch and Seo 1987;Kaneda and others 1989;Irwing and others 1991;Gales 2000). Oxygen is considered the most adverse factor on beer quality (Irwing and others 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Grigsby and Palamand (1976) reported that TBA (thiobarbituric acid) values correlated with extent of beer staling. Lynch and Seo (1987) indicated the measurement of ethylene in headspace of beer was useful for following beer staling. Schmitt and Hoff (1979) also reported that acetaldehyde concentration in beer correlated with mean panel scores for stale flavor.…”
Section: Introductionmentioning
confidence: 99%